Retrospective analysis of mepivacaine, prilocaine and chloroprocaine for low-dose spinal anaesthesia in outpatient perianal procedures - Gebhardt, Volker; Kiefer, Kevin; Weiß, Christel; Schmittner, Marc (International journal of colorectal disease, 2018)
PurposePerianal procedures are carried out in an outpatient setting regularly. The purpose of this retrospective analysis was to investigate the impact of different local anaesthetics (LA) for spinal anaesthesia (SPA) on operating room (OR) efficiency (perioperative process times, turnaround times) and postoperative recovery. This study aims on the determination of the optimal LA for low-dose SPA in the specific setting of a high-volume day-surgery centre.MethodsAnaesthesia records of all patients undergoing perianal outpatient surgery under saddle-block SPA at the Mannheim University Medical Centre from 2008 until 2017 were analysed. Patients were categorized as having received prilocaine, mepivacaine or chloroprocaine.ResultsTwo thousand seven hundred forty-six patients were included. Postoperative recovery was faster for chloroprocaine 1% compared with both other LAs. Preoperative processes but not process times in the OR were shorter for chloroprocaine. In contrary, turnaround times were significantly prolonged when chloroprocaine had been used, leading to reduction of OR efficiency.ConclusionLow-dose SPA provides reliable blocks for perianal surgery. Considerations on the choice of LA for SPA must include not only the recovery profile, but also the impact on OR efficiency. Due to shorter turnaround times and a manageable prolonged duration of stay, prilocaine is the preferable LA for low-dose SPA in perianal outpatient surgery at a high-volume day-surgery centre.
Gesehen am 16.10.2019